ANALISIS PENYELESAIAN TUGAS PROBABILITAS SISWA SD DITINJAU DARI PERBEDAAN KEMAMPUAN MATEMATIKA DAN GENDER - dwi ivayana sari; I Ketut Budayasa; dwi juniati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study is aimed to analyze probabilistic thinking of elementary school students based on math ability and gender differences. Descriptive explorative approach was used to describe in depth probabilistic thinking of boys with high, middle, low math ability and girls with high, middle, low math ability. The result showed that probabilistic thinking of boy with high math ability indicated multistructural because his thinking quantitative and proportional. While probabilistic thinking of boys with middle, low math ability and girls with high, middle, low math ability indicated unistructural because their thinking quantitative and non proportional. Beside that, boys’ thinking in solving probability tasks was more analytical and flexible than girls’ thinking. So, students with math ability difference, gave difference response in solving probability tasks. This result found new strategy in solving probability comparison task. This result could contribute to curriculum developer to introduce probability in elementary school level and teachers could use discussion method in teaching probability material.